Soil organic and phytomass carbon stocks in mountain periglacial settings of Vindelfjällen (Sweden) - Christina Fröjd; Berta González Sánchez; Peter Kuhry (Arctic, Antarctic, and Alpine Research)
We present a detailed soil organic carbon (SOC) and phytomass carbon (C) inventory for a mountain periglacial region in northwest Sweden (altitude range c. 600–1,800 m). We describe plant cover and soil profiles at thirty-nine sites representing the main land cover classes at and above tree line. The mean landscape-level SOC storage for full soil depth is 7.14 kg C m−2, which includes 35 percent of high-alpine ice/snow and bare ground surfaces with negligible SOC stocks. The main SOC hotspots are boreal (maximum stock of 118.5 kg C m−2) and alpine (maximum stock of 79.9 kg C m−2) wetlands. Solifluction lobes in the alpine belt hold above average but highly variable SOC stocks (2.11–19.5 kg C m−2). Permafrost was only encountered in small remnants of collapsing palsas, holding negligible SOC stocks. Mean phytomass C storage is 0.36 kg C m−2, with birch forest storing on average about twenty times more phytomass C (4.41 kg C m−2) compared to the mean for the upland alpine tundra classes (0.20 kg C m−2). Projected increases in ambient temperatures will likely result in an upward shift of the tree line and the alpine vegetation belt with a potential increase in phytomass C and SOC stocks.